National Animosity and Cross-Border Alliances - Arikan, Ilgaz; Shenkar, Oded (Academy of Management Journal, 2013)
We extend the cross-border strategic alliance knowledge base by introducing dyad-specific antagonism (animosity between nation pairs) and hold that the formation and the type of firm-level cross-border alliances are nontrivially impacted by conflicting relations and animosity between their home nations. We examine the formation of alliances between firms among nation-dyads with and without a history of conflicts. The frequency and magnitude of conflicts increase the perception of likelihood of opportunism, and dyad-specific risks materially affect the context in which firms make alliance decisions. As animosity between two nations increases, the number and the probability of forming alliances within the dyad the nations form decreases. Conditional on the expected number of alliances, increased antagonistic actions of nations outside the dyad and dissimilarity in the historical conflicts that each nation has engaged in outside the dyad (i) increase the number of equity alliances and (ii) decrease the number of nonequity alliances as a proportion of total alliances. We find positive main effects of learning to contract through prior experience only for equity (vs. nonequity) alliances. The reputation effects of antagonism based on relationships with nations outside of the dyad negatively moderate the positive learning effects of prior equity alliance experience.